2009
DOI: 10.1021/pr9006156
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Proteomics Profiling of Lipid Rafts in CCR6-Activated T Cells Reveals the Integration of Actin Cytoskeleton Dynamics

Abstract: Chemokines orchestrate leukocyte migration toward sites of inflammation and infection and target leukocytes via chemokine receptors such as CCR6, a subfamily of the seven-transmembrane G-protein-coupled receptors. Lipid rafts are cholesterol and sphingolipid-enriched liquid-ordered membrane microdomains thought to serve as scaffolding platforms for signal transduction. To globally understand the dynamic changes of proteins within lipid rafts upon CCR6 activation in T cells, we quantitatively analyzed the time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 93 publications
1
47
0
Order By: Relevance
“…Another possible mechanism underlying the modulation of the expression of this chemokine receptor might involve lipid rafts, membrane-bound microdomains that are enriched with cholesterol, sphingolipids, and saturated fatty acids and that function as a scaffolding platform for a variety of cellular functions, including signal transduction events (57). It has recently been shown that cholesterol depletion of CCR6-expressing Jurkat T cells impairs CCL20-mediated CCR6 signaling, suggesting that lipid rafts are necessary for CCR6 activation (58). It can therefore be postulated that Ag-specific activation of CCR6-expressing T cells might result in a remodeling of the distribution of CCR6 at the cell surface, a subsequent exclusion of the receptor from the rafts and transport to clathrin-coated pits, thereby facilitating its internalization in the endosome and its subsequent degradation by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism underlying the modulation of the expression of this chemokine receptor might involve lipid rafts, membrane-bound microdomains that are enriched with cholesterol, sphingolipids, and saturated fatty acids and that function as a scaffolding platform for a variety of cellular functions, including signal transduction events (57). It has recently been shown that cholesterol depletion of CCR6-expressing Jurkat T cells impairs CCL20-mediated CCR6 signaling, suggesting that lipid rafts are necessary for CCR6 activation (58). It can therefore be postulated that Ag-specific activation of CCR6-expressing T cells might result in a remodeling of the distribution of CCR6 at the cell surface, a subsequent exclusion of the receptor from the rafts and transport to clathrin-coated pits, thereby facilitating its internalization in the endosome and its subsequent degradation by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…However, quantitative changes in protein levels are not covered by this approach and are also of functional importance in signal transduction. Quantitative proteomic approaches dissecting antigen receptor-mediated dynamics of DRMs have been reported [11,35,36]. However, these studies were performed on material obtained from cell lines and have been based mostly on metabolic labeling of cells by differential feeding with light or heavy isotopic amino acids, an approach which is not possible with primary cells.…”
Section: Qualitative Analysis Of the Drm Proteomementioning
confidence: 99%
“…Proteomic raft analysis can be achieved by extracting these domains from the plasma membrane (Foster et al, 2003, Jordan & Rodgers, 2003, Lin et al, 2010, Mannova et al, 2006, Nebl et al, 2002. Isolation of membrane rafts was traditionally performed in cold, non-ionic detergent, such as Triton X-100, in which raft proteins are largely insoluble (Brown & Rose, 1992).…”
Section: Visualizing Protein Heterogeneity Within Membrane Vesiclesmentioning
confidence: 99%